2021
DOI: 10.3390/ijms22094303
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia: A Unique Disorder of Bone Mineralization

Abstract: Hypophosphatasia (HPP) is a rare genetic disease characterized by a decrease in the activity of tissue non-specific alkaline phosphatase (TNSALP). TNSALP is encoded by the ALPL gene, which is abundantly expressed in the skeleton, liver, kidney, and developing teeth. HPP exhibits high clinical variability largely due to the high allelic heterogeneity of the ALPL gene. HPP is characterized by multisystemic complications, although the most common clinical manifestations are those that occur in the skeleton, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 111 publications
0
47
0
3
Order By: Relevance
“…HPP is most commonly caused by heterozygous or compound heterozygous mostly missense (about 74%) mutations at the ALPL gene [ 65 ]. The mode of inheritance refers to an autosomal dominant or recessive manner, with the most severe phenotypes being transmitted with the autosomal recessive trait, whereas the milder forms are transmitted with either the dominant or recessive trait [ 19 ].…”
Section: Diagnosis and Counselingmentioning
confidence: 99%
See 2 more Smart Citations
“…HPP is most commonly caused by heterozygous or compound heterozygous mostly missense (about 74%) mutations at the ALPL gene [ 65 ]. The mode of inheritance refers to an autosomal dominant or recessive manner, with the most severe phenotypes being transmitted with the autosomal recessive trait, whereas the milder forms are transmitted with either the dominant or recessive trait [ 19 ].…”
Section: Diagnosis and Counselingmentioning
confidence: 99%
“…In general, the severe phenotypes of HPP are usually caused by homozygous or compound heterozygous mutations [ 66 ] and manifest as a recessive disease. In cases of mild or moderate forms with autosomal dominant inheritance the underlying mechanisms involve either a dominant negative effect of a single heterozygous mutation, intronic mutations, or mutations in the regulatory sequence [ 65 , 67 ]. In European patients it has been shown that 13.4% of the HPP-affected chromosome alleles have a dominant negative effect [ 3 ].…”
Section: Diagnosis and Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, a mutation in the gene coding for TNSALP has been closely associated with a severe skeletal deformity disease termed “hypophosphatasia (HPP),” which is characterized by several pathological abnormalities, including rickets, osteomalacia, epilepsy-like seizures associated with vitamin B6 deficiency, muscle weakness, and respiratory disturbance [ 14 , 15 ].…”
Section: General Property Of Alkaline Phosphatase (Alp)mentioning
confidence: 99%
“…4 Generally, teeth and skeletal mineralization disorders are the most common symptoms of HPP patients and less common clinical presentations include musculoskeletal abnormalities, multiple fractures, fatigue, and migraine. 5 HPP is classified into the following groups based on severe to mild symptoms since before birth to adulthood: perinatal lethal HPP, prenatal benign HPP, infantile HPP, childhood HPP, adult HPP, and ordontohypophosphatasia. 6 Lethal perinatal is the most severe subtype of HPP characterized by deformed and shorted arms and legs, deformity of the chest during delivery because of skeletal mineralization blocking due to low alkaline phosphatase level.…”
Section: Introductionmentioning
confidence: 99%